2006
DOI: 10.1530/eje.1.02087
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of tall stature in boys with somatostatin analogue 201–995: effect on final height

Abstract: Background: An optimal treatment for tall stature in boys in terms of efficacy and safety is not available. Treatment with somatostatin analogue 201 -995 (SMS) has been tried with positive short-term results. Methods: We evaluated the effect of SMS treatment on reducing adult height. Over 2 years, 16 boys presenting to our university hospital with tall stature (constitutional tall stature (n ¼ 13), Marfan syndrome (n ¼ 2) and tethered spinal cord (n ¼ 1)) with a predicted final height above 197 cm were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Somatostatin analogs have shown to cause a modest height reduction. One promising study with long-acting lanreotide demonstrated a mean height reduction of 3.8 cm; however, this treatment is still considered experimental (97,98). Pegvisomant, a GH receptor antagonist, has not yet been studied as a growth reduction treatment in patients with tall stature without GH excess.…”
Section: Treatmentmentioning
confidence: 99%
“…Somatostatin analogs have shown to cause a modest height reduction. One promising study with long-acting lanreotide demonstrated a mean height reduction of 3.8 cm; however, this treatment is still considered experimental (97,98). Pegvisomant, a GH receptor antagonist, has not yet been studied as a growth reduction treatment in patients with tall stature without GH excess.…”
Section: Treatmentmentioning
confidence: 99%
“…It has been reported that a nocturnal infusion of octreotide, a somatostatin analogue (201–995), reduces GH secretion and height prediction in tall children [ 42 , 43 ]. However, a more recent study, showed that long-term treatment with analogue of somatostatin (201–995) does not reduce final height in a manner sufficient to justify the treatment in tall stature [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of excessively tall stature with high doses of sex steroids is a well-known, though controversial, therapy [1,2,3,4,5,6,7]. In boys, high doses of testosterone are used to reduce final height.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are no studies comparing the effects of two different doses of testosterone on final height in tall boys [3,4]. Therefore, we compared the effects of 250 versus 500 mg testosterone enanthate every 2 weeks on near final height in boys with constitutional tall stature.…”
Section: Introductionmentioning
confidence: 99%